PERCEPTION OF SPECIAL AND GENERAL EDUCATION TEACHERS REGARDING PRACTICES AND CHALLENGES IN ADAPTING CURRICULUM FOR STUDENTS WITH DIVERSE LEARNING NEEDS: A MIX METHOD STUDY (Al-Aasar, 2026)
The present mixed-method study explored the perceptions of special and general education teachers regarding their practices and challenges in adapting curriculum for students with diverse learning needs.  The teacher survey was conducted among 99 teachers with the help of the structured questionnaire consisting of the Likert-scale and open-ended items. Quantitative data indicated that teachers are highly using inclusive interventions of differentiated instructions, scaffolding, and constant evaluation with mean scores of 3.85 to 4.22. Nevertheless, educators indicated that they encountered moderate to strong difficulties, especially in balancing curriculum requirements and multiple needs of students (M = 3.85), in working with large classes (M = 3.77), and in resource shortage (M = 3.67). The qualitative results were characterized by the necessity to focus on student-based curricula, training of teachers, and technology integration. The research concludes that despite positive attitudes and practices of teachers towards inclusion, there exist systemic barriers to having a successful implementation. The findings emphasize the need for institutional support, flexible curriculum frameworks, and professional development to enhance inclusive education.